FXYD3 (Mat-8), a New Regulator of Na,K-ATPase - Crambert, Gilles (The American Society for Cell Biology, 2005)
Four of the seven members of the FXYD protein family have been identified as specific regulators of Na,K-ATPase. In this study, we show that FXYD3, also known as Mat-8, is able to associate with and to modify the transport properties of Na,K-ATPase. In addition to this shared function, FXYD3 displays some uncommon characteristics. First, in contrast to other FXYD proteins, which were shown to be type I membrane proteins, FXYD3 may have a second transmembrane-like domain because of the presence of a noncleavable signal peptide. Second, FXYD3 can associate with Na,K- as well as H,K-ATPases when expressed in Xenopus oocytes. However, in situ (stomach), FXYD3 is associated only with Na,K-ATPase because its expression is restricted to mucous cells in which H,K-ATPase is absent. Coexpressed in Xenopus oocytes, FXYD3 modulates the glycosylation processing of the β subunit of X,K-ATPase dependent on the presence of the signal peptide. Finally, FXYD3 decreases both the apparent affinity for Na(+) and K(+) of Na,K-ATPase.